2010
DOI: 10.1021/cm903785r
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy to Synthesis of Hierarchical Mesoporous Zeolites

Abstract: We report a new strategy to synthesize the hierarchical mesoporous zeolite through design of mesoscale cationic surfactant cetyltrimethylammonium bromide (CTAB) micelle with cosolvent tertbutyl alcohol (TBA) and the 1,3,5-trimethylbenzene (TMB) additive, by which the formation of hierarchical mesostructure arose from the condensing of zeolite fragments on the mesoscale surfactant micelles. The hierarchical mesoporous silica with zeolite Y or sodalite fragment is synthesized for the first time, which exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 52 publications
(89 reference statements)
3
85
0
Order By: Relevance
“…[10][11][12][13][14] The synthetic elegance of bottom-up methods is counteracted by a low chance for industrialization, since they commonly necessitate the use of costly and commercially unavailable reactants as mesopore-inducing agents, [15][16][17][18][19] and/ or lead to products not easily separated from the mother liquor, e.g., nano-crystals or nano-sheets. [19,20] On the other hand, top-down approaches such as demetallation are highly effective and scalable at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The synthetic elegance of bottom-up methods is counteracted by a low chance for industrialization, since they commonly necessitate the use of costly and commercially unavailable reactants as mesopore-inducing agents, [15][16][17][18][19] and/ or lead to products not easily separated from the mother liquor, e.g., nano-crystals or nano-sheets. [19,20] On the other hand, top-down approaches such as demetallation are highly effective and scalable at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…Among which, introducing mesopores into the original structure of microporous zeolites is one of the most efficient methods [5][6][7]. Such mesostructured zeolite materials have not only the advantages of micropores, which ensure acidity and shape selectivity, but also the advantages of mesopores, which promote the adsorption of molecules [8][9][10] and diffusion rate for mass transfer within zeolites [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous Y zeolite can also be obtained using surfactant templates [33][34][35][36][37][38][39][40]. Garcia-Martinez et al reported about the scale-up of a surfactant-templated process to prepare mesoporous Y zeolite; composite catalysts based on such hierarchical zeolite Y showed improved yield of valuable gasoline and light cycle oil (LCO) products over bottoms and coke in FCC catalyst evaluation [41].…”
Section: Introductionmentioning
confidence: 99%